2022
DOI: 10.1021/acs.energyfuels.1c03615
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Adequate Circulation in Chemical Looping Combustion─Design Proposal for a 200 MWth Chemical Looping Combustion Circulating Fluidized Bed Boiler

Abstract: Chemical looping combustion (CLC) has unique potential for avoiding the large costs and energy penalties of existing CO 2 capture technologies. Oxygen is transferred to the fuel using an oxygen carrier, thus avoiding contact between air and fuel. Consequently, the combustion products, CO 2 and H 2 O, come in a separate stream, and more or less pure CO 2 is obtained after condensation of H 2 O. CLC is normally conceived as a dual fluidized bed process, with high gas velocities in an air reactor driving the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…Thus, the effect of the temperature, circulation, and fuel flow could not be assessed. (2) This also means that, in contrast to LD slag, there was no oxidation to NO for the cases when CO was zero.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effect of the temperature, circulation, and fuel flow could not be assessed. (2) This also means that, in contrast to LD slag, there was no oxidation to NO for the cases when CO was zero.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 12 , 13 These investigations have shown that CLC provides an efficient and cost-effective method for the combustion of gaseous fuels with inherent capture of CO 2 . 14 …”
Section: Introductionmentioning
confidence: 99%
“…The CLC process implicitly reduces the energy penalties of separating CO 2 and other products associated with a traditional air-based combustion. This technology for the combustion of gaseous fuels, particularly natural gas, has been an active research area for the last two decades. ,, These investigations have shown that CLC provides an efficient and cost-effective method for the combustion of gaseous fuels with inherent capture of CO 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology uses gasphase O 2 , generated by metal oxides such as those of copper, to react with the solid fuel directly, through comparatively fast solid-gas reactions. In the past two decades, pilot megawatt-scale CLC reactors have been developed [22][23][24][25] , showing great promise for industrial scale decarbonization.…”
mentioning
confidence: 99%